2017
DOI: 10.1186/s12906-017-2035-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sesamin on primary human synovial fibroblasts and SW982 cell line induced by tumor necrosis factor-alpha as a synovitis-like model

Abstract: BackgroundRheumatoid arthritis (RA) is an autoimmune disease that causes chronic synovitis, cartilage degradation and bone deformities. Synovitis is the term for inflammation of the synovial membrane, an early stage of RA. The pathogenesis of the disease occurs through cytokine induction. The major cytokine that increases the severity of RA is TNF-α. Thus, inhibition of the TNF-α cascade is an effective way to diminish the progression of the disease. We are interested in investigating the difference between pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…Although the mobility of OA patients appeared to be very limited and painful due to inflammation [32]. We confirmed that MS and γ-MS treatment improves the mobility significantly by subjecting treated and nontreated mice to an open field test to record their movement.…”
Section: Therapeutic Effect Of γ-Mssupporting
confidence: 69%
“…Although the mobility of OA patients appeared to be very limited and painful due to inflammation [32]. We confirmed that MS and γ-MS treatment improves the mobility significantly by subjecting treated and nontreated mice to an open field test to record their movement.…”
Section: Therapeutic Effect Of γ-Mssupporting
confidence: 69%
“…The significant inhibition of SGE on synovial hyperplasia and inflammation on rats inspired us a further investigation into the therapeutic effects and mechanisms on the human fibroblast-like synoviocytes. The best-known cell model used to study synovitis in RA is the human synovial sarcoma cell line (SW982) [20]. Hence, we validated the effects and mechanisms of SGE on human SW982 synovial cell.…”
Section: Discussionmentioning
confidence: 94%
“…The significant inhibition of SGE on synovial hyperplasia and inflammation on rats inspired us a further investigation into the therapeutic effects and mechanisms on the human fibroblast-like synoviocytes. The best-known cell model used to study synovitis in RA is the human synovial sarcoma cell line (SW982) [19]. Hence, we validated the effects and mechanisms of SGE on human SW982 synovial cell.…”
Section: Discussionmentioning
confidence: 94%